Evaluating Technical and Human Factors in Management - Gosselin, Emile (Relations industrielles / Industrial Relations, 1952)
SummaryIn order to produce, a coordinated system is necessary of which the complexity varies in accordance with the needs of those participating, the nature of the product or the size of the market. In this system, the needs and the production steps determine the exact place of each element, men and machines, in the structure. This coordination requires from each part of the whole, definite operations and the coordination of all the efforts towards the accomplishment of the enterprise's object. What are these principles capable of assuring harmonious relations during the production ?